RESILIENT COMMUNITIES: TURNING DISASTER INTO BLESSING FROM ENVIRONMENTAL LESSONS - Sofia, Sofia; Sahidah, Ahmad; Sain, Zohaib Hassan (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Abstract:Floods have been a recurring challenge for the people of Kedungdalem Village, Dringu District. This study explores community resilience by identifying social and environmental factors that influence their ability to adapt and recover. It also examines the application of environmental-based learning to reduce the impact of flooding and evaluates local strategies in disaster management to create social and economic sustainability. Using a qualitative approach through in-depth interviews, field observations, and document analysis, this study found that reliance on traditional lifestyles, inadequate waste management, and limited infrastructure were the main contributors to flooding. The results show the important role of community organizations such as Fatayat NU and the Village Consultative Body (BPD) in raising community awareness and mobilizing resources for environmental education and disaster preparedness. Strategies such as mutual cooperation efforts in maintaining water channels have had a positive impact. However, challenges remain in integrating modern techniques with traditional practices and overcoming economic constraints. The study concludes that increasing environmental awareness and leveraging local solidarity are key to turning disasters into opportunities for sustainable community growth. These findings contribute to the discussion on community-based disaster resilience and offer practical recommendations for integrating local wisdom with modern environmental management practices.